2010
DOI: 10.1542/peds.2009-1116
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy Knowledge, Attitudes, and Beliefs of Primary Care Physicians

Abstract: WHAT THIS STUDY ADDS:We surveyed more than 400 primary care physicians and found that knowledge of food allergy was fair, with several important opportunities for improvement identified. Of particular interest, respondents expressed concern regarding their ability to care for affected children. abstract OBJECTIVE: To provide insight into food allergy knowledge and perceptions among pediatricians and family physicians in the United States. METHODS:A national sample of pediatricians and family physicians was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
4
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 29 publications
6
90
4
3
Order By: Relevance
“…Pediatricians who participated in the study mentioned above stated that the poor adherence rates are often due to a lack of familiarity with management guidelines and uncertainty about the pediatrician's role in food allergy management. 6 Although physician knowledge was noted to increase as a result of the educational intervention, this increased knowledge did not improve physician practice. Potential reasons for the lack of change in physician practice may be issues of time constraints and difficulty navigating within the EMR.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Pediatricians who participated in the study mentioned above stated that the poor adherence rates are often due to a lack of familiarity with management guidelines and uncertainty about the pediatrician's role in food allergy management. 6 Although physician knowledge was noted to increase as a result of the educational intervention, this increased knowledge did not improve physician practice. Potential reasons for the lack of change in physician practice may be issues of time constraints and difficulty navigating within the EMR.…”
Section: Discussionmentioning
confidence: 96%
“…The rates of allergy referrals, epinephrine prescriptions, and emergency action plans at our clinic were similar to a recent study of general pediatricians, which showed that 67% of children diagnosed with food allergies are referred to an allergist, 45% are given a prescription for injectable epinephrine, and emergency action plans are provided to 6%. 6 On average, pediatricians comply with the NIAID food allergy management guidelines in two of five areas. Pediatricians who participated in the study mentioned above stated that the poor adherence rates are often due to a lack of familiarity with management guidelines and uncertainty about the pediatrician's role in food allergy management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants did not have prior knowledge on the objectives of the study. The survey consisted of some questions that were mainly based on the validated questionnaire and guidelines (13,14). The questionnaires included questions on the demographic characteristics of the participants and their knowledge and attitudes regarding the symptoms, severity, triggers, some hidden food content such as dairy, eggs and management of food allergies including the effects of cooking methods on food allergenicity and procedures causing crosscontact.…”
Section: Methodsmentioning
confidence: 99%
“…12 One exception is Finland, with its National Allergy Program which includes standardised approaches and systematic educational efforts. 13 Consequently, several European bodies are currently focusing their efforts in either standardising, or lobbying for, improved allergy education in both specialist and primary care.…”
mentioning
confidence: 99%